Keefektifan Isolat Tunggal, Campuran dan Konsorsium Bakteri Endofit terhadap Fusarium solani dan Meloidogyne spp. secara in Vitro - r jahuddin, resky wulandari; Munif, Abdul; Sukarno, Bonny Poernomo Wahyu; Gusmaini, Gusmaini (Jurnal Fitopatologi Indonesia, 2022)
Effectivity of Single Isolates, Mixtures, and Consortium of Endophytic Bacteria Against Fusarium solani and Meloidogyne spp. in VitroFusarium solani and Meloidogyne spp. is known as pathogens associated with pepper yellow disease. The use of endophytic bacteria for controlling this disease needs to be evaluated. Therefore, this study was conducted with the aim of evaluating the biocontrol activity of endophytic bacterial isolates applied singly (B. siamensis and B. velezensis), mixed (B. subtilis and B. wiedmannii) and consortium (PTM3) in suppressing F. solani and Meloidogyne spp. in vitro. Research methods included the isolation of F. solani and extraction of Meloidogyne spp. from the roots of infected plant, pathogenicity test, dual culture and mortality test, as well as physiological assay of endophytic bacterial isolates. The isolates of F. solani and Meloidogyne spp. proven to be pathogenic in pepper seedlings and causing yellow symptoms. Four isolates of endophytic bacteria were able to inhibit mycelium growth of F. solani. The highest inhibition on TSA medium was shown by a single isolate of B. siamensis, i.e. 57.25%; while on PDA medium was shown by mixed isolates of B. subtilis and B. wiedmannii, i.e. 56.47%. Application of B. velezenziz caused the highest mortality rate of Juvenile larval 2 Meloidogyne spp., i.e. 75.24%. Both B. siamensis and B. velevenzis isolates showed protease and cellulase activity; while mixed isolates of B. subtilis and B. wiedmannii and the PTM3 consortium isolates showed chitinase, protease and cellulase activity.